1994
DOI: 10.1152/jappl.1994.77.4.1736
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise decreases progression of muscular dystrophy in diaphragm of mdx mice

Abstract: Effects of voluntary wheel running on contractile properties of diaphragm (DIA) and soleus (SOL) of dystrophic (mdx) and control (C57BL/10SNJ) mice were evaluated. In particular, we tested the hypothesis that daily voluntary running is not deleterious to muscle function in mdx mice. Both groups of mice ran extensively (control mice approximately 7 km/day, mdx mice approximately 5 km/day). Exercise increased maximal specific tetanus tension of mdx DIA from 1.02 +/- 0.04 to 1.33 +/- 0.06 kg/cm2 but did not resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 0 publications
11
85
2
Order By: Relevance
“…In the mdx mouse, a transgenic model with significant muscle degeneration/regeneration and muscle pathology, there is conflicting evidence regarding the effects of exercise. Specifically, voluntary wheel running has been shown to increase muscle force output and decrease muscle fatigability (16,23), whereas eccentric exercise has been shown to be significantly more damaging to mdx muscle than to control muscle (11). An additional question regarding the MHC null mice, therefore, was whether wheel-running activity would affect the muscle pathology observed in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the mdx mouse, a transgenic model with significant muscle degeneration/regeneration and muscle pathology, there is conflicting evidence regarding the effects of exercise. Specifically, voluntary wheel running has been shown to increase muscle force output and decrease muscle fatigability (16,23), whereas eccentric exercise has been shown to be significantly more damaging to mdx muscle than to control muscle (11). An additional question regarding the MHC null mice, therefore, was whether wheel-running activity would affect the muscle pathology observed in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous experimental exercise protocols, in which voluntary running resulted in shorter running distances for mdx than for genetically unaffected mice [8,15], the exercise protocol used in the present investigation was standardised for both control and mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Barton et al (4) have shown that overexpression of insulin-like growth factor I in mdx mice augments muscle mass and reduces fibrosis within the diaphragm. Second, there is evidence that short-term strength or endurance training is useful for reducing the loss of diaphragmatic force-generating capacity and increased muscle fatigability associated with dystrophin deficiency (8,10,50). However, there has also been a fear that training could increase the level of contraction-induced injury and hence satellite cell turnover, thereby leading to an accelerated decline of regenerative potential (39).…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%